Can more public information raise uncertainty? The international evidence on forward guidance - Michael Ehrmann; Gaetano Gaballo; Peter Hoffmann; Georg Strasser (European Central Bank (ECB), 2019)
Central banks have used different types of forward guidance, where the forward guidance horizon is related to a state contingency, a calendar date or left open-ended. This paper reports cross-country evidence on the impact of these different types of forward guidance on the sensitivity of bond yields to macroeconomic news, and on forecaster disagreement about the future path of interest rates. We show that forward guidance mutes the response to macroeconomic news in general, but that calendar-based forward guidance with a short horizon counterintuitively raises it. Using a model where agents learn from market signals, we show that the release of more precise public information about future rates lowers the informativeness of market signals and, as a consequence, may increase uncertainty and amplify the reaction of expectations to macroeconomic news. However, when the increase in precision of public information is sufficiently large, uncertainty is unambiguously reduced.
Keywords: D83; E43; E52; E58; 330; central bank communication; heterogeneous beliefs; forward guidance; disagreement; macroeconomic news